Comparison of the matrix effect in laser induced breakdown spectroscopy analysis of coal particle flow and coal pellets. Issue 11 (11th October 2021) - Yu, Ziyu; Yao, Shunchun; Jiang, Yuan; Chen, Weize; Xu, Shuixiu; Qin, Huaiqing; Lu, Zhimin; Lu, Jidong
Abstract : Laser-induced breakdown spectroscopy analysis of coal particle flow presents milder matrix effect compared with coal pellet. Abstract : Laser-induced breakdown spectroscopy (LIBS), as a promising analytical technique for coal analysis, is greatly affected by the matrix effect. Existing studies have a fundamental understanding of the matrix effect in coal pellets, but the matrix effect in coal particle flow has never been studied previously. This paper aims to characterize the matrix effect in the coal particle flow and compares it with that in the coal pellets. Using seven coal samples with similar carbon content but different matrices, we investigate the spectral analytical response of C I 247.86 nm to the carbon content. Additionally, the ablation crater profiling method and the fast-imaging approach have been applied to characterize the ablation mass and the laser thermal effect, followed by the in-depth analysis of the matrix effect in coal particle flow. The experimental results show that particle flow analysis can ensure stable ablation mass and alleviate the laser thermal effect. Based on these improvements, LIBS analysis of particle flow reveals a milder matrix effect compared with pellets, reducing the inconsistency of spectral analytical response from 21.64% to 12.87%.